Discovery of selective dengue virus inhibitors using combination of molecular fingerprint-based virtual screening protocols, structure-based pharmacophore model development, molecular dynamics simulations and in vitro studies - Mirza, SB (Elsevier BV, 2020)
10.1016/j.jmgm.2017.10.010